2016
DOI: 10.1089/fpd.2015.1969
|View full text |Cite
|
Sign up to set email alerts
|

Salmonellosis Hospitalizations in the United States: Associated Chronic Conditions, Costs, and Hospital Outcomes, 2011, Trends 2000–2011

Abstract: Hospitalized salmonellosis patients with concurrent chronic conditions may be at increased risk for adverse outcomes, increasing the costs associated with hospitalization. Identifying important modifiable risk factors for this predominantly foodborne illness may assist hospitals, physicians, and public health authorities to improve management of these patients. The objectives of this study were to (1) quantify the burden of salmonellosis hospitalizations in the United States, (2) describe hospitalization chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Findings from this study also showed that the incidence of laboratory-confirmed Salmonella infection is similar in the senior age group and younger adults. This is consistent with data from other industrialized countries that show peaks in childhood rate and similar rate in adult age groups [ 7 , 20 ] Nonetheless, salmonellosis in seniors is often associated with more severe consequences than younger adults [ 21 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Findings from this study also showed that the incidence of laboratory-confirmed Salmonella infection is similar in the senior age group and younger adults. This is consistent with data from other industrialized countries that show peaks in childhood rate and similar rate in adult age groups [ 7 , 20 ] Nonetheless, salmonellosis in seniors is often associated with more severe consequences than younger adults [ 21 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…; Cummings et al . ). Even in developed countries, the disease may be serious enough to lead to death, particularly in vulnerable populations, and yet the mechanisms underpinning the development of diarrhoea have remained poorly understood.…”
Section: Introductionmentioning
confidence: 97%
“…Poultry is the most significant contributor to food-borne Salmonellosis in humans (62). Colonization of chickens with Salmonella results in a rapid (less than 4 h) inflammatory response that evolves into an asymptomatic, persistent infection during which time the bacterium is continuously shed in feces (63).…”
Section: Salmonella (Ex Vivo)mentioning
confidence: 99%